The endocannabinoid system modulates the ovarian physiology and its activation can improve in vitro oocyte maturation. Issue 10 (20th March 2020) - Totorikaguena, Lide; Olabarrieta, Estibaliz; Lolicato, Francesca; Romero‐Aguirregomezcorta, Jon; Smitz, Johan; Agirregoitia, Naiara; Agirregoitia, Ekaitz
Abstract: The cannabinoid (CB) system has been involved in many aspects of reproduction and it is known that the systemic chronic use of exogenous CBs are deleterious to reproductive processes. Even so, it is not known what happens in relation to the physiology of the ovary when CB receptors are absent. The present study investigated the effect of the lack of CB1 and CB2 receptors in mice ovarian morphology, folliculogenesis, oocyte retrieval, and oocyte maturation and evaluated the use of Δ9‐tetrahydrocannabinol (THC) on oocyte in vitro maturation (IVM) by comparing classical IVM and two‐step IVM by analyzing the meiotic competence of the oocytes and their evolution toward embryos. Thus, when CB1 and CB2 receptors were missed, the ovary area and volume was significantly less and the action of the equine chorionic gonadotropin (eCG) hormone was diminished. In addition, the mutant genotypes had fewer ovarian follicles and they were less competent after eCG administration compared with wild‐type mice, and this lack of CB receptors showed a mismatch of oocyte maturation. However, the in vitro use of THC showed improvements in oocytes IVM after a Pre‐IVM step for 48 hr, as those oocytes reached a significantly higher polar body rate, a larger diameter and the best result on blastocysts rate was achieved when THC was used during the IVM step. Abstract : The lack of cannabinoid 1 (CB1) and/or CB2 receptor in knockout (KO) models impairs ovarian morphology, folliculogenesis, oocyte retrieval, and oocyte maturation. And, the use of CBs in vitro can be beneficial as modulators of some processes.